Examining the relationship between green innovation dynamics and firm performance: a comparative study of BRICS and G7 countries - Nirupam Mukhopadhyay; Narayan Chandra Nayak (Cogent Business & Management, 2024)
Green innovation entails the production assimilation or exploitation of unique methods of doing business that result in a decrease in environmental risks. Green innovation is a complex and multifaceted process, encompassing product, process, and organizational dimensions, each with unique factors influencing firm performance, business efficiency, and sustainable development. This research investigates the impact of eco-innovation on the financial performance of firms across 12 G7 and BRICS countries from 2013 to 2022. Considering 2100 listed firms, the study explores how process, product, and organizational eco-innovation dimensions affect business performance. Utilizing Feasible Generalized Least Square (FGLS) regression and System Generalized Method of Moments (GMM) models, the results indicate a positive impact of environmental innovation on firm performance. Further, in BRICS countries, process, and organizational eco-innovations have greater impacts, while in G7 countries, product eco-innovation gets precedence. The varying impacts reflect the unequal stages of development and priorities between the two groups. It also signifies that G7 countries possess more resources for green innovation, while BRICS countries are still evolving. The findings therefore underscore the importance of tailored regulations, monitoring, and support to facilitate the integration of eco-innovations into business processes. Moreover, there is a need for firms to adopt and execute green innovation-based economic activities that would make them financially efficient, and strengthen the growth imperatives of both the groups of countries. Collaboration between developed and emerging economies would go a long way fostering common goals across them.
Keywords: 650; Firm performance; green innovation; organizational eco-innovation; product eco-innovation; process eco-innovation; BRICS; G7